Research on Starbucks Brand Value Marketing in China's Coffee Industry - Kang, Lina; Bi, Chuanchen (Technium Social Sciences Journal, 2022)
"I'm not at Starbucks, I'm on my way to Starbucks.". This catchphrase is not only a fast-paced lifestyle, but also an attitude toward life in the coffee age. Coffee is so ubiquitous that it is sought after by urban white-collar workers and petty bourgeoisie. The main reason why Chinese consumers freshly ground coffee has evolved from the initial social scene demand to the daily functional demand. The top three reasons for Chinese consumers to drink coffee are physiological refreshing, psychological dependence and coffee intake for meals. With the gradual formation of the coffee habit, most consumers have become physically and psychologically dependent on coffee, and coffee has therefore appeared in more and more daily work and life scenes. This paper takes the Starbucks brand "providing consumers with a third living space" as the research object, starting with SWOT analysis of marketing strategies and value propositions, and through qualitative research methods (unstructured interview), aiming at Starbucks brand marketing, brand value, the current development status in China's first tier cities and how to better to tell the Starbucks story in the future, I hope to provide suggestions for the sustainable and healthy development of the coffee industry.